Barrel electroplating of Zn-Ni alloy coatings from a modified deep eutectic solvent. (4th March 2022) - Lei, C.; Skouby, H.; Kellner, R.; Goosey, E.; Goosey, M.; Sellars, J.; Elliott, D.; Ryder, K. S.
ABSTRACT: Here the authors report the electroplating of Zn-Ni alloy on mild steel components from a modified deep eutectic solvent (DES), Ethaline, through a combination of barrel-plating and pulse-plating processes. The Ethaline electrolyte, a eutectic mixture of choline chloride (ChCl) and ethylene glycol (EG), was modified with propylene carbonate (PC) as a co-solvent together with the addition of boric acid to control deposit morphology and to suit the barrel plating system. A coating of γ-phase Zn-Ni alloy with 12–16% Ni was formed uniformly on mild steel screws and small components and the coating performed well as a sacrificial anti-corrosion layer. These findings are reported as part of an Innovate UK funded collaboration between university and industry partners, and included here are also the results of a scale-up pilot demonstrator system installed at E.C. Williams Ltd. (UK). It is concluded that the barrel plating of components using these materials and methods is very effective on a medium-scale and that the specification and performance of the coating is comparable with that from aqueous media. However, further development of this process may be limited by low current efficiency and the high relative cost of DES media.